Fast encoding algorithm based on Weber's law and Triangular Inequality Theorem - A. Karam, Nihad; A. Hameed, Maha; A. Hamdan, Suhad (Iraqi Journal of Science, 2023)
In the present work, an image compression method have been modified by combining The Absolute Moment Block Truncation Coding algorithm (AMBTC) with a VQ-based image coding. At the beginning, the AMBTC algorithm based on Weber's law condition have been used to distinguish low and high detail blocks in the original image. The coder will transmit only mean of low detailed block (i.e. uniform blocks like background) on the channel instate of transmit the two reconstruction mean values and bit map for this block. While the high detail block is coded by the proposed fast encoding algorithm for vector quantized method based on the Triangular Inequality Theorem (TIE), then the coder will transmit the two reconstruction mean values (i.e. H&L) with an index of codeword instead of bit map (binary block) after designation binary codebook. In other word, the proposed method enables a sensible decrease of the bit rate with fast in codebook searching, little deterioration of performance, edge preservation, good decoded image quality with greatly decreasing the matching searching time, consequently simplify the computational complexity.